2007
DOI: 10.1042/cs20060274
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and enzymatic basis of bone resorption by human osteoclasts

Abstract: Although much has been learned recently of the mechanisms that regulate osteoclastic differentiation, much less is known of the means through which their resorptive activity is controlled. This is especially so for human osteoclasts. We have recently developed an assay that allows us to measure resorptive activity while minimizing confounding effects on differentiation by optimizing osteoclastogenesis, so that measurable resorption occurs over a short period, and by relating resorption in each culture during t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 41 publications
2
26
0
Order By: Relevance
“…81,82 Both IL-6 and IL-8 are known to attract and activate osteoclasts and to play a role in prostate cancer. 49,53,83,84 Osteoclast formation by PC3-derived IL-6 and IL-8 was recently shown to be RANKL-independent. 53 Our results suggest a RANKL-dependent interaction between IL-8 and cathepsin K, but not between IL-6 and cathepsin K. Given the importance of cathepsin K for osteoclast differentiation and function, 55,56 further studies will be needed to validate the contribution of cathepsin K-mediated secretion of pro-inflammatory factors to osteolysis and progression of prostate tumors in the bone.…”
Section: Discussionmentioning
confidence: 99%
“…81,82 Both IL-6 and IL-8 are known to attract and activate osteoclasts and to play a role in prostate cancer. 49,53,83,84 Osteoclast formation by PC3-derived IL-6 and IL-8 was recently shown to be RANKL-independent. 53 Our results suggest a RANKL-dependent interaction between IL-8 and cathepsin K, but not between IL-6 and cathepsin K. Given the importance of cathepsin K for osteoclast differentiation and function, 55,56 further studies will be needed to validate the contribution of cathepsin K-mediated secretion of pro-inflammatory factors to osteolysis and progression of prostate tumors in the bone.…”
Section: Discussionmentioning
confidence: 99%
“…In the sealed resorption lacuna, localized acidification is driven by carbonic anhydrase II and vacuolar H(+)-ATPase in osteoclasts; carbonic anhydrase II produces protons and vacuolar H(+)-ATPase transfers them into the lacuna. In acidified lacuna, cathepsin-K and matrix metalloproteinase-9 (MMP-9) are released from osteoclasts to degrade calcified tissues [9]. …”
Section: Osteoclasts Are Formed From Monocytes Stimulated By Ranklmentioning
confidence: 99%
“…Bone slices with purified mature osteoclasts were transferred to new wells and incubated for an additional 3 days with M-CSF, TNF-␣, and IL-1␣ with or without different concentrations of IL-3. The resorption activity in bone cell culture supernatants was determined by quantifying CTX-I by CrossLaps ELISA (29). We found that IL-3 had no effect on CTX-I in mature osteoclasts (data not shown).…”
Section: Effect Of Il-3 On Bone Resorption By Mature Osteoclasts and mentioning
confidence: 99%
“…a CrossLaps ELISA kit (29). One-step ELISA was performed according to the manufacturer's instructions (Nordic Bioscience Diagnostics).…”
Section: Crosslaps Elisamentioning
confidence: 99%